LITERARY CURATION AT PIBID OF PORTUGUESE AT UFRJ AND COLÉGIO PEDRO II (PERcursos Linguísticos, 2021)
The choice of literary works to be read at school - or literary curation - is a task that presupposes great power on the part of teachers and educational systems (BAJOUR 2012; ANDRUETTO 2017; COLOMER 2017). It is not a neutral gesture, because we choose and discard, we say whether such work will be part of the school canon or not. Around the choice of a book a series of questions arise for teachers: students' interests, degree of maturity of the readers, themes and problems to be discussed, important genres in the school tradition, recommendations of official documents, school curricula, market interests editorial among others. In the midst of all this, the literary and aesthetic quality of the works should also be prioritized so that students have a significant contact with literature and literary education (BAJOUR 2012; ANDRUETTO 2017; COLOMER 2017). We believe that the discussion of criteria for choosing literary works (curation) is an important knowledge to be developed during the academic life of future teachers. All of these issues raised here were widely discussed throughout PIBID in the partnership that was established between UFRJ and Colégio Pedro II. Here we present some considerations on the subject and some results obtained.